On innovations of the multivariable fractional Hardy-type inequalities on time scales - Akin, Lutfi; Zeren, Yusuf (YILDIZ TECHNICAL UNIV, 2023)
Fractional integral-type inequalities, dynamic equations, integral operators and variable expo-nents have an important place in time scales theory and harmonic analysis. Our main goal in this study is to obtain the multivariable fractional Hardy-type integral inequality using a new version of Jensen's inequality for super-quadratic and sub-quadratic functions on time scales with variable exponents.
Keywords: Time Scales; Jensen's Inequality; Fractional Hardy-Type Inequalities; Engineering